Endoscopic retrograde cholangiopancreatography training using a silicone simulator fabricated using a 3D printing technique (with videos) - Suk Pyo Shin; Kyong Joo Lee; Min Je Sung; Jong Chan Kim; Guk Bae Kim; Moo Yeop Kim; Sung Yong Han; Sung Ill Jang; Mamoru Takenaka; Chang-Il Kwon (Scientific Reports)
Abstract Endoscopic retrograde cholangiopancreatography (ERCP) training remains challenging. This study used 3D printing techniques to develop and optimize a portable ERCP training simulator and to implement basic and advanced practical techniques. Subsequently, we aimed to determine whether endoscopy trainees acquired proficiency in ERCP techniques and assess any improvements in their skill levels from using this model. An ERCP training model was generated using 3D printing techniques, including five distinct interchangeable and transparent ampullar–common bile duct (CBD) modules. A prospective study using this model was conducted with ten trainees. The technical success rate and examination times for duodenoscope insertion and biliary cannulation were evaluated. In addition, the successful plastic-stent insertion rate and trainee satisfaction were measured. The success rates for duodenoscopy, cannulation, and plastic stent insertion were 94, 100, and 92%, respectively. The mean satisfaction scores for duodenoscope insertion, cannulation, and plastic stent insertion were 4.4, 4.7, and 4.6 on a 5-point scale, respectively. Five attempts decreased the insertion time (R = − 0.591, P < 0.001) and cannulation time (R = − 0.424, P = 0.002). This ERCP-training silicon model is durable, simulates ERCP techniques easily, and helps trainees improve their ERCP techniques.